2008
DOI: 10.1158/0008-5472.can-08-1053
|View full text |Cite
|
Sign up to set email alerts
|

Brn-2 Represses Microphthalmia-Associated Transcription Factor Expression and Marks a Distinct Subpopulation of Microphthalmia-Associated Transcription Factor–Negative Melanoma Cells

Abstract: The origin of tumor heterogeneity is poorly understood, yet it represents a major barrier to effective therapy. In melanoma and in melanocyte development, the microphthalmia-associated transcription factor (Mitf) controls survival, differentiation, proliferation, and migration/metastasis. The Brn-2 (N-Oct-3, POU3F2) transcription factor also regulates melanoma proliferation and is up-regulated by BRAF and B-catenin, two key melanoma-associated signaling molecules. Here, we show that Brn-2 also regulates invasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

19
279
4
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(303 citation statements)
references
References 26 publications
19
279
4
1
Order By: Relevance
“…Interestingly, BRN-2 (POU3F2), which belongs with Oct4 (POU5F1) to the POU domain transcription factor family, functions at the cross road between ERK and WNT pathways. BRN-2 identifies in some melanoma, a population of Mitf negative cells with increased invasive properties (Goodall et al, 2008). Intravital imaging study revealed a reversible switching between poorly differentiated, BRN-2-high and highly pigmented BRN-2-low melanoma cells (Pinner et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, BRN-2 (POU3F2), which belongs with Oct4 (POU5F1) to the POU domain transcription factor family, functions at the cross road between ERK and WNT pathways. BRN-2 identifies in some melanoma, a population of Mitf negative cells with increased invasive properties (Goodall et al, 2008). Intravital imaging study revealed a reversible switching between poorly differentiated, BRN-2-high and highly pigmented BRN-2-low melanoma cells (Pinner et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…This pathway is also involved in the regulation of melanin synthesis. It has been reported that activation of MEK/ERK leads to phosphorylation of MITF at serine 73, resulting in its degradation [28,38] . The PI3K⁄Akt pathway plays an important role in cell growth regulation and apoptosis inhibition [39,40] .…”
Section: Discussionmentioning
confidence: 99%
“…In this context, mTOR inhibition has also been shown to suppress the outgrowth of clones with resistance to MAPK inhibition 126 . Finally, in those melanomas in which MITF expression is not restored 132 , many receptor tyrosine kinases can be upregulated and contribute to the resistant phenotype 133,134 (FIG. 4a).…”
Section: Braf-mek-inhibitor Resistance and Biomarkersmentioning
confidence: 99%